Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 2. realistic form, so that it can be examined and tested by the country both from the standpoint of administrative feasibility and also from the standpoint of cost. (5) Our only regret is that there has been a great tendency in the Press and in public discussion to urge the Government for an immediate acceptance of the principles of the Report without allowing time for the calm and deliberate consideration and examination which the subject deserves. On that aspect, we feel it right to point out that the activities of the Federations which constitute the Confederation's membership are at this time necessarily concentrated on the vital and urgent questions of production necessary for the winning of the war. It has therefore not been possible for them, in the few weeks which have elapsed since the "Beveridge" Report was issued, to examine in detail the full implications of the proposals and, in particular, the far-reaching questions of principle which Sir William suggests Parliament should meanwhile adopt by a series of Resolutions. (6) It may well be that on further consideration we may be able to find a considerable measure of agreement on certain of these principles. So far, however, such examination as we have been able to make, would seem to show that these questions of principle are so closely interwoven with questions of application - such as the rates and conditions of Benefit and the financing of these Benefits - that we do not think the subject can be dealt with by a series of Resolutions without committing the country to principles, the application and cost of which, when the details are filled in, might well prove impracticable. (7) Meanwhile, there is one important issue which we feel should be focussed at the outset of this Memorandum, namely, how far the Report's conception of Social Security is limited to the objective of the Abolition of Want, and how far it aims at a second and wider objective in its proposals for providing Benefits, Allowances, Services and Grants as a legal right to sections of the community which are not in Want. (8) So far as the first objective is concerned - the Abolition of Want - we hold the view that it is essential to abolish Want so far as it exists, and that the abolition of Want must be given a first place in our post-war obligations/ 200/B/3/2/C216/5/50